UPAYA MENINGKATKAN HASIL BELAJAR DAN MENGANALISIS PEMBERONTAKAN DI/TII DI BERBAGAI DAERAH DENGAN PENERAPAN MODEL PEMBELAJARAN INQUIRY - Rasto; Endang Sedianingrum (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2023)
This classroom action research aims to apply the Inquiry learning model to increase motivation and learning outcomes to analyze DI/TII rebellions in various regions for class XII students. 1 IPS SMA Negeri 1 Filled in the odd semester of the 2022/2023 academic year. Research The model used is the experimental method. This research was conducted in two cycles, each cycle consisting of four activities, namely planning, implementation, observation, and reflection. The results of this classroom action research show that the learning motivation of students in cycle 1 in the discussion activity has an average value of 68 (category C) and in cycle 2 it has increased to an average value of 81 (category A). While the learning motivation of students at the time of presentation in cycle 1 the average value was 69 (category C) and in cycle 2 it increased to an average value of 83 (category A). Then for the indicators of student learning outcomes, the research is said to be successful if the students who complete in cycle 1 are 48% (16 people), and the results of research in cycle 2 have increased, namely students who have completed to 82% (27 people).